Applicability of Regulation 1215/2012 («Brussels I bis») to an unexecuted employment contract: ECJ 25 February 2021 (c-804/2019) - Juárez Pérez, Pilar (CUADERNOS DE DERECHO TRANSNACIONAL, 2022)
The ECJ deals with an unprecedented case in its jurisprudence: the eventual applicability of Regulation 1215/2012, of December 12 (Brussels I bis) to a dispute regarding an employment contract where the labor provision has not been executed, for reasons attributable to the employer. Despite the absence of such effective execution, the ECJ determines that the forums of international jurisdiction contained in the Brussels I bis Regulation are fully and exclusively applicable to the litigation, since it is a case that meets its criteria of material and personal application. The consequence of the applicability of Brussels I bis Regulation is the displacement of the States rules of international judicial competence, due to the provisions of its articles 4.5 and 5. Consequently, it is not possible to activate state forums -even when they may be more beneficial to the worker-, since the community rules on judicial jurisdiction in this matter are not only special, but also exhaustive.